Radiation damage in tungsten target of the "KIPT Neutron Source" - Gann, V.V.; Gann, A.V.; Borts, B.V.; Karnaukhov, I.M.; Gladkikh, P.I.; Parkhomenko, A.A. (Вопросы атомной науки и техники, 2021)
In this work, mathematical modeling of a complex of processes occurring in a tungsten target under irradiation with high-energy electrons with an energy of 100 MeV: an electromagnetic shower, the production of photo-neutrons, and particle transport along the target, damage from neutrons of the subcritical assembly. It was found that the greatest contribution to the rate of damage formation in a tungsten target give the elastic scattering of high-energy electrons on nuclei.